La organización social de los mazahuas del Estado de México - González Ortiz, Felipe (CIENCIA ergo-sum; Vol. 8 Núm. 1 (2001): CIENCIA ergo-sum (marzo-junio 2001), 2015)
This work is a comparative study of several Mazahua communities experiencing varying degrees of cultural erosion. It refers to the social links established between the nuclear family, the extended family through the paternal line and the traditional civic religious hierarchies that form one kind of social organization peculiar to the Mazahua ethnic group. This group posits their cosmological bases on a cultural matrix dating back to pre columbian and colonial times. Notwithstanding the presence of that cultural matrix, the communities manifest different kinds of social organization that the author perceives as having evolved as a consequence of the destructuration of the system of kinship. The origin of that system resides in the social differentiation leading to new forms of organization, that priviledge the ritual kinship over the kinship of blood ties.